Macro-based asset allocation: An empirical analysis - Miroslav Kollar; Christian Schmieder (European Investment Bank (EIB), 2019)
Macro-based asset allocation, i.e., the identification of turning points in macro-financial cycles and the allocation of assets accordingly, has attracted a lot of interest in recent years. This interest was sparked by volatile financial markets, more synchronized returns across asset classes and countries as well as the low interest rate environment. A horse-race among different asset allocation strategies suggests that macro-based asset allocation informed by trends in continuous indicators characterizing the business and financial cycle could be a promising alternative for medium- and long-term investment. Despite changes in the relationship between macro-financial cycles and asset price cycles during the last three decades, the most promising specifications did roughly anticipate turning points in asset price cycles, resulting in favorable returns and low portfolio volatility. The authors appreciate the promising role of this approach, but urge caution given the complexity of the inherent interactions.
Keywords: E32; E37; G11; 330; Asset Allocation; Macro-based; Financial cycle; Business cycle; Long-term